Evolving Teacher Roles in Artificial Intelligence-Driven Learning: A Phenomenological Study in Social Studies Education - Isaac Deonwel G Falcis; Maricar U Juaneza (Journal of Social Knowledge Education (JSKE), 2026)
Purpose of the study:This study examined how Araling Panlipunan (Social Studies) teachers perceive and experience the integration of Artificial Intelligence in their instructional practice, focusing on public secondary schools in Matalam, Cotabato to capture localized insights on digital adaptation in rural contexts. Methodology: Using a phenomenological qualitative design, purposively selected teachers were interviewed through semi-structured conversations to explore their lived experiences with Artificial Intelligence tools, and thematic analysis was applied to identify recurring patterns in their narratives. Main Findings: Findings revealed that teachers view Artificial Intelligence as a helpful and efficient instructional assistant, particularly in lesson planning, content enrichment, and generating teaching strategies that support engagement and provide diverse, updated resources. Despite these advantages, teachers emphasized AI’s limitations in addressing students’ emotional and social needs, concerns about content accuracy, and challenges related to technical access and reliability. The discussion highlights that while Artificial Intelligence is perceived as a valuable supplement to teaching, it cannot replace the essential human capacities of creativity, discernment, ethical judgment, and contextual understanding that underpin effective instruction. Novelty/Originality of this study: The study underscores the need for context-sensitive professional development, clearer institutional guidelines, and supportive infrastructure to ensure that Artificial Intelligence strengthens rather than undermines teacher agency and the human dimension of Social Studies education.